Pengajaran Konsep Keselamatan Pada Jemaat di GPP Pohan Tonga - Meletios Pakpahan; Kallistratos Rumabutar; Immanuel Lumbantoruan; Reni Herayani Manik; Jeicca Melati Siregar; Anessa Mei Pasaribu; Adi Suhenra Sigiro (Jurnal DIKMAS, 2024)
This study aims to explore the teaching and concept of safety applied to the congregation at GPP Pohan Tonga. Research was conducted through interviews with pastors and congregation members to understand the teaching approach and understanding of salvation applied in the church context. The research results show that teaching at GPP Pohan Tonga is based on in-depth and applicable Bible teaching. The church pastor emphasized the importance of a solid understanding of Biblical teachings and the application of Christian values in daily life. The concept of salvation is understood as a gift of God's grace received through faith and repentance, and realized in a life of obedience and serving others. The congregation at GPP Pohan Tonga is actively involved in a variety of church services and religious activities, demonstrating their commitment to growing in faith and expanding Christian influence within their community. Church pastors play a crucial role in guiding, serving, and caring for congregants on their faith journey. The teachings and concepts of salvation applied to the congregation at GPP Pohan Tonga reflect the church's commitment to strengthening the foundations of faith, expanding understanding of God's grace, and encouraging congregation members to live according to the teachings of Christ. This research provides valuable insight into teaching practices and spirituality in the church, and provides a foundation for better ministry development and spiritual growth in the future.